Economic backwardness and economic growth : studies in the theory of economic development - Leibenstein, Harvey (New York ; London : Wiley, 1957)
This book consists of a series of analytical essays designed to explain the persistence of income differences between economies in different stages of economic growth and development.
One of a series of books from the research program of the Institute of Industrial Relations, University of California.
Includes bibliographical references and index.
lje 18/05/2018
Loans
Keywords: Economic development; Economic history; Economic growth; Developing countries